Research perspectives of the cultural expertise in the context of formation of the urban cultural space - I. V. Zhyvohliadova (Ukrainian Cultural Studies, 2020)
The article analyzes the spectrum of objects and problems in the context of the cultural space of the city that may (and need) be the subject of attention of expert activities in the field of culture. The issue of culturological expert knowledge is considered in the context of the process of optimizing the use of the urban cultural capital, removing restrictions on access to its resources, and creating tools to struggle with the "business-colonization of culture". It is argued that cultural expertize can become a transversal mechanism and a tool of finding the optimal analytical assessment of the relationships, their intersections, deep structures, all kinds of chronotopes that are inherent in the modern city.